Book Review for The Power of Morality in Movements: Civic Engagement in Climate Justice, Human Rights, and Democracy - David Brockway (Journal of Community Engagement and Scholarship)
Review of the book: Anders Sevelsted and Jonas Toubøl (Eds.), The Power of Morality in Movements: Civic Engagement in Climate Justice, Human Rights, and Democracy. Springer, 2022, 334 pages. ISBN: 978-3-030-98797-8 (eBook). https://doi.org/10.1007/978-3-030-98798-5